TRENDS IN THE DEVELOPMENT OF TECHNOLOGIES AND THEIR INFLUENCE ON MANAGEMENT OF INDUSTRIAL ENTERPRISES - A. V. Nikonorova (Вестник университета)
The article examines the influence of the development of modern technologies on the management of industrial enterprises. The paper considers the main trends in the development of technologies, shows the dynamics of their changes over the past three years. The strongest positions in the market are  held by companies that have determined the right vector for their development on time, and adaptation as a reaction to the emergence of new technologies becomes the key factor for successful functioning of an industrial enterprise in turbulent environment. The article presents a model of management for industrial enterprises heeding trends in development of technologies, and for the first time submits the usage of systems for preliminary assessment of innovation technology for its compliance and non-contradiction to the interests of the individual.